The role of social participation in municipal-level health systems: the case of Palencia, Guatemala - Ana Lorena Ruano (Taylor & Francis Group, 2013)
Background: Social participation has been recognized as an important public health policy since the declaration of Alma-Ata presented it as one of the pillars of primary health care in 1978. Since then, there have been many adaptations to the original policy but participation in health is still seen as a means to make the health system more responsive to local health needs and as a way to bring the health sector and the community closer together. Objective: To explore the role that social participation has in a municipal-level health system in Guatemala in order to inform future policies and programs. Design: Documentary analysis was used to study the context of participation in Guatemala. To do this, written records and accounts of Guatemalan history during the 20th century were reviewed. The fieldwork was carried out over 8 months and three field visits were conducted between early January of 2009 and late March of 2010. A total of 38 in-depth interviews with regional health authorities, district health authorities, community representatives, and community health workers (CHWs) were conducted. Data were analyzed using thematic analysis. Results: Guatemala's armed civil struggle was framed in the cold war and the fight against communism. Locally, the war was fed by the growing social, political, and ethnic inequalities that existed in the country. The process of reconstructing the country's social fabric started with the signing of the peace agreements of 1996, and continued with the passing of the 2002 legal framework designed to promote decentralization through social participation. Today, Guatemala is a post-war society that is trying to foster participation in a context full of challenges for the population and for the institutions that promote it. In the municipality of Palencia, there are three different spaces for participation in health: the municipal-level health commission, in community-level social development councils, and in the CHW program. Each of these spaces has participants with specific roles and processes. Conclusions: True participation and collaboration among can only be attained through the promotion and creation of meaningful partnerships between institutional stakeholders and community leaders, as well as with other stakeholders working at the community level. For this to happen, more structured support for the participation process in the form of clear policies, funding and capacity building is needed.